Creative Merchandise Design for Tourists based on Luoshan Shadow Puppet Elements through Visual Rhetoric - Taotao, Xu (Xu Taotao, 2024)
The main aims of this study are to establish systematic methods for designing creative merchandise of Luoshan shadow puppet by incorporating a visual rhetorical approach as a guiding tool for designers. This study considers the unique features of Luoshan shadow puppet and applies the principles and methods of visual rhetoric (VR) to enhance their visual expression and market competitiveness. In Luoshan shadow puppet creative merchandise design (LSPCMD), visual rhetoric (VR) methods help designers convey their products’ storytelling, artistry, and cultural connotations. This study also addresses the issue of neglected innovations in Luoshan shadow puppet creative merchandise. Mixed research method is the research method used in this study. To assess the feasibility of visual rhetoric in influencing these types of merchandise design, survey data are obtained from Intangible Culture Heritage (ICH) experts, academicians, designers, and users of creative merchandise in China. A design practice involving creative children's dinner plate is applied using Luoshan shadow elements after conducting semi-structured interviews and surveys in the form of a questionnaire. This is followed by a second questionnaire to validate the results of design practice. It is found that visual rhetoric (VR) has a significant influence on the design situation, design creativity, and design method of Luoshan shadow creative merchandise through visual rhetorical situations (VRS), visual rhetorical structures (VRST), and visual rhetorical strategies (VRSG). These findings expand the knowledge of sustainable design research for such goods by considering how visual rhetoric (VR) influences these merchandise designs. The findings provide designers insights into design inspirations and creative directions within visual culture. Finally, the study presents limitations and suggestions for future research. Recommendations include: (a) highlighting the characteristics of traditional shadows, (b) creating visual impact, (c) considering the user experience, and (d) paying attention to sustainability. In conclusion, this thesis offers a comprehensive reference to local staff designing merchandise using visual rhetorical methods.